The uniqueness of the German barracks in the context of the style of military architecture in the interwar period - Rudnicka-Bogusz, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
When studying the styles of barracks complexes in Eastern Europe, one can notice two main periods of heightened militarism. The large-scale barracks built in the 1880s represent a style infused with national romanticism. In Prussia, for example, it is Rundbogenstil, which legitimizes monarchical power. As a result of the defeat in World War I, this style is compromised. With the beginning of the 1930s, the tendency to build extensive barracks complexes intensifies again.
Keywords: nationalism; Heimatstil; Heimatschutz; military architecture; architecture; 1918-1939